LVRT Reactive Current Index of Renewable Units Based on the Constraints of Transient Voltage - Hui LIU; Kuo WANG (Zhongguo dianli)
The renewable power gathering system often presents the characteristics of a weak AC grid. And the voltage fluctuates greatly during the failure process. The problem of renewable units being turned-off due to low voltage and transient overvoltage is prominent. This paper establishes the voltage-current relationship of the renewable power gathering system. Considering the safety constraints of low voltage and transient overvoltage, we gives the LVRT reactive current index requirements for the renewable units through theoretical derivation. Then, the renewable power gathering system is classified according to the short circuit ratio (SCR), and for systems with different SCRs, differentiated LVRT reactive current index requirements are given.